AGILE LEADERSHIP AT START-UP CARA BICARA - Oktavia Erlina Dwi , Anggraini; Rita, Mutiarni (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
An agile leadership style is an approach that is responsive to business change, with transparency, collaboration, and adaptability. This leadership style suits current business conditions and is open to active and dynamic participation from all organization members. This research is intended to look at the application of Agile leadership in the â€œCara Bicaraâ€ strategy. This research used a qualitative approach to obtain complete information about Agile leadership by leaders at the start-up " Cara Bicara.â€ Data collection techniques were carried out using observation, documentation, and interviews with 5 (five) informants who were leaders of the â€œCara Bicaraâ€ team. From the research results, it can be seen that the leadership of â€œCara Bicaraâ€ has implemented the Agile Leadership model well, which is reflected in 1) Providing individual Support, team trust, and conflict resolution; 2) Actively involved in decision-making; 3) Exploring team potential and team mentoring; 4) Manage differences of opinion in the team; 5) work efficiency and effectiveness using multitasking teams, priority scale, and agility and 6) Simulations in the field, project base, weekly meetings, and expertise to increase innovation.